THE PROFILE OF PRIMARY ENGLISH TEACHERS IN INDONESIA - B. Yuniar Diyanti; Lusi Nurhayati; Nury Supriyanti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
After the implementation of the 2013 national curriculum which excludes English from the primary school, many primary schools in Indonesia keep offering English to the students despite the uncertainty of the status of English for the primary school. However, the state of the practice of English currently in primary schools is barely unknown. This study is an attempt to portray the teachers that strive to teach English in the primary schools in one of the regencies that are still implementing English education. This survey study involved 44 randomly selected Primary English teachers (PETs) in the regency. The research instrument was a set of online (google format) and offline questionnaires. Results show that the majority of the teachers have English teaching qualification, however only very few ever attended pre-service or in-service training for teachers of young learners. The teachers also deal with employment uncertainty as primary English has no formal legal government policy. The findings bring about the issue of gaps and opportunities for professional developments of PETs and inequality in professional supports for PETs. Keywords: English for young learners (EYL), primary English, primary English teacher (PET) PROFIL GURU BAHASA INGGRIS SEKOLAH DASAR DI INDONESIA AbstrakSetelah penerapan Kurikulum 2013 yang tidak mengikutsertakan bahasa Inggris sebagai mata pelajaran pilihan muatan lokal (mulok) dalam kurikulum Sekolah Dasar (SD), banyak SD di Indonesia yang tetap menyelenggarakan pembelajaran bahasa Inggris dalam suasana ketidakpastian. Tidak diketahui kondisi pembelajaran bahasa Inggris di SD saat ini. Penelitian ini berusaha untuk menggambarkan guru-guru bahasa Inggris yang berjuang untuk tetap mengajarkannya di salah satu kabupaten di Indonesia yang tetap mengizinkan pembelajaran bahasa Inggris di SD. Penelitian survei ini melibatkan 44 guru bahasa Inggris SD yang dipilih secara acak dan instrumen yang digunakan adalah seperangkat kuesioner daring (googleform) dan luring (cetak). Hasil penelitian menunjukkan bahwa mayoritas guru memiliki latar beakang pendidikan bahasa Inggris, namun hanya sedikit sekali yang pernah mengikuti pelatihan pengajaran bahasa Inggris bagi anak-anak. Guru-guru tersebut juga menghadapi ketidakjelasan status kepegawaian yang disebabkan tidak adanya aturan pemerintah yang jelas tentang bahasa Inggris di SD. Temuan penelitian mengangkat isu tentang kesenjangan pada pengembangan professional guru bahasa Inggris SD dan ketimpangan dalam dukungan profesional bagi guru-guru tersebut. Kata Kunci: bahasa Inggris bagi anak-anak (EYL), bahasa Inggris di SD, dan guru bahasa Inggris SD